Short-term curative effect of endovascular stent-graft treatment for aortic diseases in China: a systematic review. - Siwen Wang; Jinsong Wang; Peiliang Lin; Zhibin Li; Chen Yao; Guangqi Chang; Xiaoxi Li; Shenming Wang (PLoS ONE, 2013)
Introduction We analyzed the short-term efficacy of endovascular treatment for aortic diseases by summarizing all available published data on endovascular stent-graft treatment for abdominal aortic aneurysm (AAA), thoracic aortic aneurysm (TAA), type A aortic dissection (type A AD) and type B aortic dissection (type B AD) in China. Methods We performed a systematic analysis of 935 published series on retrograde endovascular treatment for aortic diseases in China from January 1996 to November 2010. Based on the inclusion criteria, 159 studies, involving a total of 5531 patients, were included. Results There were no significant differences in procedural success among the studies (P>0.05). The rates of overall neurologic complications and stroke were significantly different in all two-group comparisons (P<0.01). The type A AD patients had the highest rates of neurologic complications (both 6.67±0.00%), and the AAA patients had the lowest rates (0.31±0.04% and 0.11±0.02%). Significant differences were noted in the rates of cardiac, renal, pulmonary and visceral complications, which were all higher in the type A AD patients than in the other three groups (P<0.01). The endoleak rate was highest in the TAA patients (19.27±5.74%) and was similar in the type A AD patients (P>0.05). A significant difference was noted between the 30-day mortality rate of the type A AD patients and the AAA or type B AD patients (P<0.05). Conclusion Endovascular stent-graft is a feasible and safe treatment for aortic diseases, with high procedural success and low incidences of post-procedural complications and short-term mortality. Endovascular treatment for AAA and type B AD is more efficient than for type A AD and TAA.